Hypopituarism - Not such an obvious symptom - Grzybek, Monika; Wilczyńska, Barbara; Kasprzak, Anna; Kułaga, Monika; Mazur-Lesińska, Diana; Szostak, Barbara; Wielgosz-Biała, Sylwia; Tyszkiewicz, Krzysztof; Łozowski, Borys; Kasprzak, Małgorzata (Journal of Education, Health and Sport, 2025)
This paper presents the case of a diagnostic and therapeutic challenge of a young 33-year-old man from Poland, who initially reported few symptoms and eventually turned out to be an interesting endocrine case The pituitary gland is the central endocrine gland that controls the entire human endocrine system. Despite its small size, it dominates over the other endocrine glands. The pituitary gland is located inside the skull, in the so-called Turkish saddle. It secretes a number of hormones: growth hormone (GH), prolactin (PRL), adrenocorticotropic hormone (ACTH), thyrotropic hormone (TSH), folliculotropic hormone (FSH), luteinizing hormone (LH), melanotropin (MSH), oxytocin, vasopressin.